Cluster Analysis for MRI Brain Tumor Segmentation (Medico Legal Update, 2020)
The abnormal tissues which are originated from the brain cells are known as brain tumor. It may be canceroustumor or non-cancerous tumor; these can cause pressure inside the skull to increase the tumors. Thisdamages the brain and become life-threatening. The main cause of brain tumor is still unknown. The earlydiagnosis is required otherwise it increases the mortality rate. The segmentation of tumor part is essentialto identify the affected area in the brain. In this study, an effective method for Brain Tumor Segmentation(BTS) is presented. The BTS system uses Discrete Wavelet Transform (DWT), K-Means Clustering (KMC)algorithm and morphological operations for segmentation. Firstly, the input brain images are given to DWTfor decomposition and it produces lower and higher frequency sub-band coefficients. Then the InverseDWT (IDWT) is applied to reconstruct the image. The reconstructed image is given to KMC techniquefor segmentation. Then the unwanted regions are removed by morphological operations to detect the braintumor in the given input image.